Method for prolonging service life of titanium alloy blade extrusion die

The hardness and wear resistance of titanium alloy blade extrusion molds are improved through salt bath nitriding treatment technology, and the serious wear of titanium alloy forged blade molds is solved. It extends the mold life and reduces production costs. It is suitable for large-scale production .

CN119120870APending Publication Date: 2024-12-13GUIZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411319061.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-21
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

Titanium alloy forged blades are severely worn by molds due to high temperature and large loads in the extrusion process, which affects the molding quality and mold life, and increases the production cost and bottlenecks in production line automation.

Method used

The salt bath nitriding treatment technology is adopted to nitride the titanium alloy blade extrusion mold in a salt bath nitriding furnace to improve the surface hardness and wear resistance of the mold, thereby extending the service life of the mold.

Benefits of technology

Through salt bath nitriding treatment, the surface hardness and wear resistance of the H13 steel extrusion mold are significantly improved, the service life of the mold is extended, the production cost is reduced, and the process operation is simplified, which is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119120870A_ABST
    Figure CN119120870A_ABST
Patent Text Reader

Abstract

The invention discloses a method for prolonging the service life of a titanium alloy blade extrusion die, and belongs to the technical field of titanium alloy blades. After the titanium alloy blade extrusion die is cleaned and subjected to salt bath nitriding treatment, the service life of the extrusion die is greatly prolonged, a remarkable effect is achieved, and salt bath chemical components of the titanium alloy blade extrusion die comprise 40% of CO (NH2) 2, 15% of Na2CO3, 15% of K2CO3, 25% of NaCl and 5% of K2SO3; and the salt bath heat preservation time is 0.5-4 hours.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0002] This invention relates to the field of titanium alloy blade technology, and in particular to a method for improving the life of titanium alloy blade extrusion dies. Background Technology

[0003] In the extrusion process of titanium alloy forged blades, the high extrusion temperature and heavy equipment load make the dies prone to wear and tear, resulting in dimensional deviations and poor surface quality of the extruded parts. This necessitates additional auxiliary processes to ensure the parts meet surface quality requirements, significantly increasing production costs. Furthermore, frequent die changes severely impact production schedules, hindering capacity increases and becoming a bottleneck for production line automation. Currently, H13 steel extrusion dies are used to manufacture titanium alloy forged blades. H13 steel extrusion dies possess excellent characteristics such as high hardenability, thermal fatigue resistance, and wear resistance. As one of the most widely used and representative hot work die steels in recent years, it is widely used in the manufacture of hot extrusion dies, mandrels, and forging dies. With increasing societal demand, H13 steel extrusion dies are now primarily used in the manufacture of various types of extrusion dies. However, in actual production, the operating environment of H13 steel extrusion dies is very complex, generally subjecting them to significant friction and impact forces, and even operating at high temperatures. When its service temperature exceeds 600℃, its thermal stability and thermal fatigue resistance are poor; when the surface is subjected to huge impacts and severe friction, cracking and frictional wear will occur. These are some of the more common failure phenomena of H13 steel molds. These adverse factors will reduce the service life and working efficiency of the molds. Summary of the Invention

[0004] In order to overcome the above-mentioned defects of the prior art, the present invention aims to provide a method for improving the surface hardness and wear resistance of titanium alloy extrusion dies through surface nitriding treatment, thereby improving the die life.

[0005] To achieve the above objectives, the present invention adopts the following technical solution: A method for improving the service life of titanium alloy blade extrusion dies includes the following steps: S1: Raw Material Preparation ① Raw material preparation: Several titanium alloy blade extrusion dies of the same specifications are machined by turning, milling, grinding and polishing, and then quenched and tempered. Finally, the extrusion dies are precision machined and polished. ②Auxiliary materials: Prepare sufficient gasoline, iron wire, and sample baskets; ③ Equipment and tooling preparation: Adjust the salt bath nitriding furnace and set its temperature to 550℃. Prepare a cooling device next to the salt bath nitriding furnace. S2: Preparation: ① The titanium alloy blade extrusion die prepared in step ① of stage S1 is placed in gasoline for cleaning to remove oil stains on the die, activate the die surface, and obtain a titanium alloy blade extrusion die with a clean surface to be treated. ② Place the extrusion die for the titanium alloy blade obtained in step ① into the sample basket prepared in step ② of stage S1, and arrange them evenly, binding and fixing them with wire; ③ After setting the holding temperature of the salt bath nitriding furnace, the chemical composition of the salt bath is: CO(NH2)2: 40%, Na2CO3: 15%, K2CO3: 15%, NaCl: 25%, K2SO3: 5%; S3: Salt bath nitriding treatment Place the sample basket from step S2 ② into a working salt bath nitriding furnace, maintain the furnace temperature at 550-560℃, hold for 0.5h to 4h, then quickly remove it and cool it through a cooling device to complete the salt bath nitriding treatment.

[0006] Preferred: In stage S3, the sample basket is kept in the salt bath for 3.5 h in the salt bath nitriding furnace.

[0007] Compared with the prior art, the present invention has the following advantages: (1) In order to ensure the forming quality of titanium alloy forged blades and extend the service life of extrusion dies, surface modification technologies have emerged continuously, including carburizing, nitriding, carbonitriding, gas oxygen-sulfur co-diffusion, boron carbonitriding, and laser cladding. Nitriding is one of the most common heat treatment processes for improving the hardness of mechanical parts. After nitriding, the surface hardness of carbon steel can reach up to 1200 HV, and the deformation of the workpiece is relatively small, and its corrosion resistance and other properties are improved. The commonly used nitriding processes are as follows: gas nitriding, ion nitriding, and salt bath nitriding. Compared with the other two processes, the salt bath nitriding equipment used in this invention has the advantages of low investment, convenient operation, and easy control. Gas nitriding and ion nitriding have relatively high investment costs. From a technical perspective, improving the fluidity and temperature uniformity of molten salt results in more uniform surface treatment quality for parts. Secondly, in terms of processing time, salt bath nitriding is relatively shorter. Gas nitriding and ion nitriding are affected by factors such as atmosphere, ammonia decomposition rate, gas pressure, and ammonia flux. Therefore, the salt bath nitriding technology used in this invention is simpler, more practical, and easier to operate than other heat treatment methods in improving the lifespan of titanium alloy blades, and can be mass-produced in factories.

[0008] (2) This invention involves salt bath nitriding of H13 steel extrusion dies. Reactive diffusion allows nitrogen atoms to penetrate the die matrix. As the holding time increases, the microstructure of the die changes. The microstructure appearing from the surface to the core of the nitrided layer is sequentially: ε phase → γ' phase → α phase. The compound microstructure of the nitrided steel part, from the surface inwards, is sequentially FeN → Fe2N → Fe3N → Fe4N. Simultaneously, a large number of dispersed alloy nitrides such as CrN, Mo2N, and VN are generated in the nitrided layer. These nitrides can enhance the wear resistance, fatigue resistance, and corrosion resistance of the H13 steel extrusion die surface.

[0009] (3) The thickness of the nitriding layer on the surface of the H13 steel extrusion die can be controlled by the nitriding and heat preservation time. According to the measured data, the thickness of the nitriding layer increases with the increase of nitriding time. Given that the H13 steel extrusion die is subjected to a lot of friction and thermal fatigue in its operating environment, the thickness of the nitriding layer must reach a certain value in order to extend the service life of the material. Attached Figure Description

[0010] Figure 1 / Figure 2 The original microstructure and original hardness of the H13 steel extrusion die after treatment in Example 1; Figure 3 / Figure 4 The diffusion layer thickness and hardness gradient of the H13 steel extrusion die after treatment in Example 2; Figure 5 / Figure 6 The diffusion layer thickness and hardness gradient of the H13 steel extrusion die after treatment in Example 3; Figure 7 / Figure 8 The thickness and hardness gradient of the infiltration layer of the H13 steel extrusion die after treatment in Example 4; Figure 9 / Figure 10 The thickness and hardness gradient of the infiltration layer of the H13 steel extrusion die after treatment in Example 5; Figure 11 / Figure 12 The diffusion layer thickness and hardness gradient of the H13 steel extrusion die after treatment in Example 6; Figure 13 / Figure 14 The diffusion layer thickness and hardness gradient of the H13 steel extrusion die after treatment in Example 7; Figure 15 / Figure 16 The diffusion layer thickness and hardness gradient of the H13 steel extrusion die after treatment in Example 8; Figure 17 / Figure 18 The thickness and hardness gradient of the infiltration layer of the H13 steel extrusion die after treatment in Example 9. Detailed Implementation

[0011] The technical solution of the present invention will now be described in detail with reference to specific embodiments, so that those skilled in the art can fully understand and implement it.

[0012] The method for improving the life of titanium alloy extrusion dies disclosed in this invention is applicable to extrusion dies made of commonly used H13 steel. Example

[0013] S1: Raw Material Preparation ① Raw material preparation: Several H13 steel titanium alloy blade extrusion dies of the same specifications are machined by turning, milling, grinding and polishing, and then quenched and tempered. Finally, the extrusion dies are precision machined and polished. ②Auxiliary material preparation: Prepare 4% nitric acid alcohol, polishing cloth and metallographic sandpaper of different grades; ③ Equipment and tooling preparation: Prepare polishing machine, metallographic sample mounting machine, micro Vickers hardness tester, optical / metallographic microscope, titanium alloy extrusion equipment, etc. S2: Preparation: ① The sample is cut from the extrusion die, mounted by a metallographic sample mounting machine, coarsely ground by metallographic sandpaper, and then finely ground on a polishing machine to remove surface scratches and dirt. The sample is then observed under an optical microscope to obtain a clean and smooth surface. ② The prepared sample was repeatedly cleaned to obtain raw material with high surface cleanliness. It was then etched with 4% nitric acid alcohol and the original structure was observed through a metallographic microscope. ③ The sample from step ② was polished with a polishing cloth and a polishing machine to obtain a clean and scratch-free sample. The hardness was measured by a micro Vickers hardness tester, and the average original hardness of the extrusion die was found to be 615 HV.

[0014] like Figure 1 As shown in Figure 2, in this embodiment, the original structure and hardness of the extrusion die were observed after cleaning and pretreatment. Example

[0015] S1: Raw Material Preparation Raw material preparation: Several H13 steel extrusion dies of the same specifications for titanium alloy blades are machined by turning, milling, grinding and polishing, and then quenched and tempered, and finally finished and polished. Preparation of auxiliary materials: Prepare sufficient gasoline, 4% nitric acid etching solution, polishing cloth and metallographic sandpaper of different grades, sample baskets, and iron wire; Equipment and tooling preparation: metallographic sample mounting machine, polishing machine, metallographic microscope and optical microscope, micro Vickers hardness tester and titanium alloy extruded bars; adjust the temperature of the salt bath nitriding furnace to maintain at 550-560℃; S2: Preparation The titanium alloy blade extrusion die prepared in step S1① is placed in gasoline for cleaning to remove oil stains from the die and activate its surface, resulting in a clean extrusion die. Place the extrusion mold to be processed obtained in step ① into the sample basket prepared in step ② of stage S1, and tie and fix it with wire; The holding temperature of the salt bath nitriding furnace has been set. The chemical composition of the salt bath is: CO(NH2)2. 40%, Na2CO3: 15%, K2CO3: 15%, NaCl: 25%, K2SO3: 5%; A cooling device with cold water is installed next to the nitriding furnace; S3: Salt bath nitriding treatment Place the sample basket containing the extrusion mold from step S2② into the prepared salt bath nitriding furnace, maintain the furnace temperature at 550-560℃, keep it at that temperature for 0.5 h, and then quickly remove it and cool it with water using a cooling device. Samples were cut from the extrusion mold after salt bath nitriding in step ① and mounted using a metallographic sample mounting machine. Then, in step S1 ②, the samples were coarsely ground and polished using metallographic sandpaper, polishing cloth, and a polishing machine. Observation under an optical microscope yielded a clean and smooth surface. After etching with a 4% nitric acid etching solution, the nitrided layer structure was observed under a metallographic microscope, and the average nitrided layer thickness of the mold was measured to be 24 μm. Finally, the sample was placed on the stage of a micro Vickers hardness tester, and hardness was measured, yielding an average surface hardness value of 998 HV.

[0016] The nitrided extrusion die was loaded into the extrusion equipment, and titanium alloy blades were extruded from titanium alloy extrusion bars until the die was destroyed, producing a total of 154 titanium alloy blades.

[0017] like Figure 3 Figure 4 shows the diffusion layer thickness and hardness gradient of the H13 steel extrusion die after treatment in this embodiment. Example

[0018] The processes of raw material preparation (S1), pre-preparation (S2), and salt bath nitriding treatment (S3) are the same as in Example 2, except that: S3: Salt bath nitriding treatment ① Salt bath nitriding and heat preservation time: 1 hour; According to the method in this example, the diffusion layer thickness was 41 μm and the average surface hardness was 1017 HV. 176 titanium alloy blades were co-extruded until the die was destroyed.

[0019] like Figure 5 Figure 6 shows the diffusion layer thickness and hardness gradient of the H13 steel extrusion die after treatment in this embodiment. Example

[0020] The processes of raw material preparation (S1), pre-preparation (S2), and salt bath nitriding treatment (S3) are the same as in Example 2, except that: S3: Salt bath nitriding treatment ① Salt bath nitriding and heat preservation time: 1.5 hours; According to the method in this example, the diffusion layer thickness was 61 μm and the average surface hardness was 1095 HV. 205 titanium alloy blades were co-extruded until the die was destroyed.

[0021] like Figure 7 Figure 8 shows the diffusion layer thickness and hardness gradient of the H13 steel extrusion die after treatment in this embodiment. Example

[0022] The processes of raw material preparation (S1), pre-preparation (S2), and salt bath nitriding treatment (S3) are the same as in Example 2, except that: S3: Salt bath nitriding treatment ① Salt bath nitriding and heat preservation time: 2 hours; According to the method in this example, the diffusion layer thickness was 88 μm and the average surface hardness was 1096 HV. 243 titanium alloy blades were co-extruded until the die was destroyed.

[0023] like Figure 9 Figure / 10 shows the diffusion layer thickness and hardness gradient of the H13 steel extrusion die after treatment in this embodiment. Example

[0024] The processes of raw material preparation (S1), pre-preparation (S2), and salt bath nitriding treatment (S3) are the same as in Example 2, except that: S3: Salt bath nitriding treatment ① Salt bath nitriding and heat preservation time: 2.5 hours; According to the method in this example, the diffusion layer thickness was 97 μm and the average surface hardness was 1126 HV. 289 titanium alloy blades were co-extruded until the die was destroyed.

[0025] like Figure 11 Figure / 12 shows the diffusion layer thickness and hardness gradient of the H13 steel extrusion die after treatment in this embodiment. Example

[0026] The processes of raw material preparation (S1), pre-preparation (S2), and salt bath nitriding treatment (S3) are the same as in Example 2, except that: S3: Salt bath nitriding treatment ① Salt bath nitriding insulation time: 3 hours; According to the method in this example, the diffusion layer thickness was 107 μm and the average surface hardness was 1173 HV. 305 titanium alloy blades were co-extruded until the die was destroyed.

[0027] like Figure 13 Figure / 14 shows the diffusion layer thickness and hardness gradient of the H13 steel extrusion die after treatment in this embodiment. Example

[0028] The processes of raw material preparation (S1), pre-preparation (S2), and salt bath nitriding treatment (S3) are the same as in Example 2, except that: S3: Salt bath nitriding treatment ① Salt bath nitriding and heat preservation time: 3.5 hours; According to the method in this example, the diffusion layer thickness was 122 μm and the average surface hardness was 1176 HV. 312 titanium alloy blades were co-extruded until the die was destroyed.

[0029] like Figure 15 Figure / 16 shows the diffusion layer thickness and hardness gradient of the H13 steel extrusion die after treatment in this embodiment. Example

[0030] The processes of raw material preparation (S1), pre-preparation (S2), and salt bath nitriding treatment (S3) are the same as in Example 2, except that: S3: Salt bath nitriding treatment ① Salt bath nitriding insulation time: 4 hours; According to the method in this example, a diffusion layer thickness of 132 μm and an average surface hardness of 1188 HV were obtained, and 310 titanium alloy blades were co-extruded until the die was destroyed.

[0031] like Figure 17 Figure / 18 shows the diffusion layer thickness and hardness gradient of the H13 steel extrusion die after treatment in this embodiment.

[0032] A comparison of Examples 2-9 with Example 1 shows that the surface hardness of the extrusion die after salt bath nitriding treatment with the salt bath composition provided by the present invention is greatly improved, i.e., the wear resistance is improved and the die life is extended. Examples 2-9 show that the hardness and the number of titanium alloy blades extruded from the die are higher when the salt bath nitriding holding time is 3.5h / 4h, i.e., the die life is longer.

[0033] The above embodiments are merely preferred embodiments of the present invention and are not intended to limit the present invention in any way. Any person skilled in the art can make many possible variations and modifications to the technical solutions of the present invention, or modify them into equivalent embodiments, without departing from the technical principles and scope of the present invention. Therefore, any combination, modification, or substitution made to the technical features disclosed in the present invention based on the technical essence of the present invention, without departing from the principles or solutions of the present invention, should fall within the protection scope of the present invention.

Claims

1. A method for improving the life of titanium alloy blade extrusion die, It is characterized in that The steps include: S1: Raw material preparation ① Raw material preparation: several titanium alloy blade extrusion dies of the same specifications are processed by turning, milling, grinding and polishing, and quenching and tempering are performed, and finally the extrusion dies are finely processed and ground and polished; ② Auxiliary materials: prepare sufficient gasoline, wire, and sample basket; ③ Equipment and tooling preparation: adjust the salt bath nitriding furnace, set its temperature at 550°C, and prepare a cooling device next to the salt bath nitriding furnace; S2: Pre-preparation: ① Put the titanium alloy blade extrusion die prepared in step ① of stage S1 into gasoline for cleaning, remove the oil stains on the die, activate the die surface, and obtain a titanium alloy blade extrusion die with a clean surface to be treated; ② Place the extrusion die of the titanium alloy blade to be processed obtained in step ① into the sample basket prepared in step ② of stage S1, and place them evenly and tie and fix them with wire; ③ Set the temperature of the salt bath nitriding furnace. The chemical composition of the salt bath is: CO(NH 2 ) 2 : 40%, Na 2 CO 3 : 15%, K 2 CO 3 : 15%, NaCl: 25%, K 2 SO 3 : 5%; S3: Salt bath nitriding Place the sample basket of step ② of stage S2 into the working salt bath nitriding furnace, maintain the furnace temperature at 550-560°C, keep it warm for 0.5h~4h, then quickly take it out and cool it through the cooling device to complete the salt bath nitriding treatment.

2. A method for improving the life of a titanium alloy blade extrusion die according to claim 1, Features: In stage S3, the sample basket is kept in the salt bath in the salt bath nitriding furnace for 3.5 h.